The Value of Kasundaan Character in Pupujian in The Book Sawér Jeung Pupujian by Ajip Rosidi: (Ethnopedagogical Study) - Marwati, Marwati (Jayapangus Press, 2025)
The increasing phenomenon of promiscuity highlights the urgent need to instill character values rooted in local wisdom, such as kasundaan. One effective medium for this is through understanding the moral values embedded in traditional pupujian texts. This research aims to (1) describe the role of pupujian in Sundanese culture, and (2) identify the kasundaan character values contained within the pupujian texts. This study uses a descriptive qualitative method with a literature review approach, focusing on the book Sawér Jeung Pupujian by Ajip Rosidi as the primary data source. The data consists of pupujian stanzas that reflect kasundaan character values. The analysis is guided by Warnaen’s theory of catur diri insan, which encompasses four pillars: pengkuh agamana (religious integrity), luhung élmuna (intellectual nobility), jembar budayana (cultural openness), and rancagé gawéna (work ethic). The findings reveal 70 stanzas containing 100 kasundaan character values. These values translate into six broader human moral principles toward God, self, others, nature, time, and the pursuit of holistic well-being. The study concludes that internalizing kasundaan character values through traditional pupujian texts can serve as a cultural strategy to foster moral resilience and promote a more meaningful life.